Spatial Analysis of Supporting Infrastructure for Coastal Tourism Areas in Province of the Special Region of Yogyakarta - Ariani, Meisy; Nursetiawan; Novendri Darimolyo, Priyo (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
Tourism has become one of the strategic drivers of regional economic growth, particularly in areas with coastal potential. As a sector that integrates multiple economic activities, tourism not only generates foreign exchange but also stimulates trade, transportation, and the development of the creative industry. This study focuses on coastal tourism areas in the Special Region of Yogyakarta. It aims to: (1) compile an inventory of coastal facilities and infrastructure (MSP), (2) analyze the spatial distribution of coastal locations (ASP), (3) assess the relationship between facility availability and visitor numbers (AFP), and (4) evaluate the accessibility of key facilities to strategic points across tourism corridors (FPL). The field inventory identified 67 facility units across beaches in Bantul and 41 units in Kulon Progo, with notable disparities in availability and service quality. Spatial analysis using ArcGIS indicates that 62% of facilities are concentrated in Bantul, an area with higher accessibility and closer proximity to the urban center, while Kulon Progo accounts for only 38%. The AFP assessment further shows a moderate positive correlation (r = 0.54) between facility completeness and visitor volume, suggesting that areas with better infrastructure tend to attract more tourists. Overall, the findings highlight the uneven distribution of coastal tourism support facilities, underscoring the need for more equitable infrastructure planning and targeted spatial development policies.